Pengenalan Inovasi Teknologi Tepat Guna “Prototype Pengendali Bagang Jarak Jauh” di Desa Barangka - Hendrawan, Nalis; Hady, Sultan; Asmiddin, Ahmad Maulid; Hamid, Helson; Azlin, Azlin (Civiliza Publishing, 2025)
Bagang is one of the traditional fishing tools used by fishermen, especially in coastal areas. However, manual bagang operations often face obstacles such as dependence on weather conditions, distance and limited human resources. To overcome these problems, it is necessary to develop a prototype of a remote bagang controller based on Internet of Thing (IoT) technology. This prototype is designed to allow fishermen to monitor and control bagang operations in real-time via mobile devices. This system consists of an ESP32 microcontroller, L298N motor driver and an integrated Android Smartphone to control bagang. The test results show that this prototype is able to operate stably at a certain distance, provide a fast response, and increase the efficiency and effectiveness of bagang management. With this technology, it is expected to help fishermen increase catch productivity and reduce operational costs.